PENGARUH KOMPETENSI TERHADAP KINERJA PENGUSAHA USAHA MIKRO KECIL (UMK) BATIK JAMBI DI WILAYAH SEBERANG KOTA JAMBI - Galih Wahyuningsih; Agustina Hanafi; Afriyadi Cahyadi (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2016)
Competence for batik Jambi entrepreneurs in micro and small-sized enterprises (MSEs) have given much attention, regarding to performance of batik Jambi entrepreneurs are decrease. This study aims to examine and analyze the influence of competence to performance of entrepreneur batik Jambi in micro and small-sized enterprises (MSEs) at region of Seberang Jambi City. This study used cencus as the sample collection method, in which the entire amount of the population used as samples. Data had been collected through distribution of questionnaires and interview. Analysis of data in this study used simple linear regression method with the help of IBM SPSS Statistics Version 22. The results of the analysis indicate that the value of R Square of 0,131, which means that competence variable was able to explain the performance variable of 13,1%. Based on these results, it can be concluded that competence has a positive and significant influence to performance of entrepreneurs batik Jambi in micro and small-sized enterprises (MSEs) at region of Seberang Jambi City.Therefore, competence is very important to improve the performance of batik Jambi entrepreneurs in micro and small size enterprises (MSEs).Keywords : Competence, Performance